Improving quality in a national intestinal failure unit: greater efficiency, improved access and reduced mortality. Issue 3 (25th August 2014) - Donaldson, Emma; Taylor, Michael; Abraham, Arun; Carlson, Gordon; Fletcher, Olivia; Varden, Jacqui; Teubner, Antje; Lal, Simon
Abstract : Problem: In 2010, there was a significant waiting list for admission to the intestinal failure unit (IFU) at the Salford Royal National Health Service (NHS) Foundation Trust. There had been a steady increase in the number of new patients referred to the IFU (89 patients 2005; 152 patients 2012) and the number of established patients requiring home parenteral nutrition (HPN) (135 patients 2005; 206 patients 2012) over the last decade. The impact of the resulting long waiting list for these complex patients was that patient deaths occurred in those awaiting admission. Design: Continuous improvement methodology using the model for improvement and sequential plan–do–study–act cycles. Setting: Salford Royal NHS Foundation Trust IFU; a large NHS teaching hospital in Northwest England. Key measures for improvement: The primary outcome measures were inpatient length of stay and time spent on waiting list prior to admission. Strategies for change: A continuous improvement programme, supported by a project manager. Results: There has been a 21% reduction in average length of stay on the IFU from 55.7 to 44.0 days and a reduction of 72% in the average length of time new patients spent on the waiting list for admission from 65.7 to 18.5 days. These changes were associated with concomitant reduction in 30-day readmission rate from 12.1% to 4.5% and early suggestions of reduced inpatient and waiting list mortality. Conclusions: It is possible to improve the efficiency of a large national service for complex patients using quality improvement methodology, resulting in improved access and reduced waiting list mortality.